Validity and Reliability of the Persian Versions of National Institute of Health Stroke Scale and Modified National Institute of Health Stroke Scale in Hospitalized Patients: - Dehghani, Reza; Borhanihaghighi, Afshin; Shariat, Abdolhamid; Nami, Mohammad; Nazeri, Masoume; Abolhasani Foroughi, Amin; Mehrabi, Samrad; Emamghoreishi, Masoumeh (Galen Medical Journal, 2019)
Background: National Institute of Health Stroke Scale (NIHSS) and Modified National Institute of Health Stroke Scale (mNIHSS) are two valid and reliable questionnaires that assess stroke severity. This study aimed to examine and compare the validity and reliability of Persian versions of NIHSS and mNIHSS in hospitalized patients. Materials and Methods: The English versions of NIHSS and mNIHSS were translated to Persian (forward and backward), and three neurologists examined the face and content validity of both questionnaires. The Persian versions of NIHSS and mNIHSS were used in75 hospitalized stroke patients (hemorrhagic and obstructive) admitted to Namazi teaching hospital, Shiraz, Iran.The reliability and validity of the Persian versions were examined by Cronbach's alpha coefficient and convergent validity. Result: The values of Cronbach's alpha for Persian versions of NIHSS and mNIHSS were 0.81 and 0.86, respectively. The scaling success of convergent validity in NIHSS and mNIHSS were 80% and 100%, respectively. Conclusion: The Persian versions of NIHSS and mNIHSS were reliable and valid. However, mNIHSS was more valid and reliable than NIHSS. Persian version of mNIHSS can be suggested to be used for assessing stroke severity in hospitalized stroke patients by neurologists and researchers. [GMJ. 2019;8:e1188]